Pengaruh Pembelajaran Berbasis Proyek dan Inkuiri Terbimbing terhadap Kemampuan Literasi Sains di Sekolah Dasar - Hana Lestari (Institut Agama Islam Sahid (INAIS) Bogor, 2021)
The purpose of this research is to find out the extent of the influence of project-based learning models and guided inquiry models on students' scientific literacy skills based on independent learning. The research was carried out at the State Elementary Schools of Cibatok 1 and Cibatok 6 Cibungbulang District Bogor Regency , with the research subjects class V students totaling 72 people. The design of this study was a post-test experimental and control group design. The method used is a quasi-experimental method (quasi-experimental). The experimental class was given the Project Based Learning (PJBL) model treatment, while the control class was given the guided inquiry model treatment. The instrument used consists of a questionnaire for independent learning and a test of scientific literacy skills. Data analysis was carried out using a two-way ANOVA test with a 2x2 factorial. Based on the results of the study, it was found that: (1) the scientific literacy skills of students who studied with the PJBL model were higher than the scientific literacy skills of students who studied with the guided inquiry model, (2) there was an interactive learning ability and independent learning model , (3) the scientific literacy ability of students who were treated with the PJBL model was higher than that of students who were treated with the guided inquiry model in groups of students who had high learning independence, and (4) there was no difference in the scientific literacy abilities of students who were given PJBL model treatment with students who were given the guided inquiry model treatment in groups of students who had low learning independence.